ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BILANGAN BULAT - diah putri islamy; Dita Mayreista; Sutinah (FKIP Universitas Tamansiswa Palembang, 2024)
This research was conducted based on the results of observations in the field showing that there are still many students who experience errors when solving story problems on integers. The aim of this research is to determine the factors that cause students' errors in solving these questions. The research was conducted 25 students on grade 7 of SMP Negeri 26 Palembang. This research is descriptive research using a qualitative approach. This research focuses on students who have low, medium and high abilities to analyze their errors. The instruments used in data collection involve field notes during practice, tests, and documentation. Based on the research results, it was found that the students' average score was 73.20, which was lower than the KKM score, which was 75. Factors in students' errors when solving story problems were that students did not understand the concept of calculating integers, students did not understand the meaning of the questions and digested them in mathematical sentences. and students are not able to do whole number calculations.